Sustainable Lean production model through alliance model in food industry - Sebastian, Lindberg (My University, 2021)
In today’s environment, the food industry is a hot topic facing continuous challenges, which creates a need to quickly adapt to different changes and demands and apply continuous improvement to its manufacturing processes. The SME businesses in the food industry are facing hard competition, and therefore, it puts pressure on creating new methods that contribute to increased sustainability in the industry as well as gaining competitive advantage from an economic perspective. The aim of the research was to examine the creation of sustainable solutions with Lean principles from a small and medium-sized (SME) approach, a combination of Lean and green collaboration methods. Lean production models such as 5R, DMAIC, and DLL are examined, and the benefits of those models in the SME food industry. As a secondary objective, this research focused on how to create more sustainable value to a product from a Lean and Green thinking approach. The research was done by gathering data on a survey with food producers and retailers. Interviews with food producers and retailers were also held. Results showed that there was a huge interest in additional digital solutions to improve the food production and distribution chain. The results also found barriers in bureaucracy and conflicts between different rules as a bottleneck in achieving full efficiency in the food production and distribution chain. The survey participants stated that the cooperation between food producers and retailers should be improved, and to reduce the food storage amounts, this to grant more fresh products, and this action would also minimize waste. New solutions in the distribution chain were presented, such as a flexible application that could be used for the transport of different products in the food production and distribution chain.
Keywords: food industry; lean manufacturing; small and medium-sized enterprises; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Systems Analytics; Sustainable Lean production model through alliance model in food industry